2009
DOI: 10.1017/s1047951109003515
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of dexmedetomidine in the paediatric cardiothoracic intensive care unit

Abstract: In this limited and retrospective review, dexmedetomidine was found to be safe and efficacious. Its use as a sedative agent for extended periods of time in critically-ill children deserves investigation in a prospective and controlled manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…31,32 Bloor et al 33 reported that after the administration of Dex, there is a decrease in the HR and biphasic blood pressure response with a short initial increase, followed by a prolonged decrease of the blood pressure. The decrease in blood pressure and HR are the result of the stimulation of central presynaptic ␣ 2a -adrenergic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Bloor et al 33 reported that after the administration of Dex, there is a decrease in the HR and biphasic blood pressure response with a short initial increase, followed by a prolonged decrease of the blood pressure. The decrease in blood pressure and HR are the result of the stimulation of central presynaptic ␣ 2a -adrenergic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The dosages observed were in alignment with the recommendations in the institution's dosing handbook and what has been reported in previous reviews of dexmedetomidine use in the pediatric critical care setting. [4][5][6]13,23 The median duration of infusion was less than 24 h, but a large group of patients received the drug for longer than 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Other studies have described no clinically significant change in hemodynamic parameters. 23,25,26 Although some patients experienced respiratory depression during dexmedetomidine therapy, the Naranjo scale score for these events was insufficient to determine dexmedetomidine as a definite or probable cause. This situation is consistent with the findings of previous studies, which have reported little or no respiratory depression with dexmedetomidine, a significant consequence of available alternative sedatives such as midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of its ␣-2 adrenergic action, the most common cardiovascular adverse effects of DEX are bradycardia and hypotension (2)(3)(4). Several reports have shown that it is associated with perioperative asystole (7,14).…”
mentioning
confidence: 99%